2018
DOI: 10.1155/2018/2438598
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells from Malignant Pleural Effusion Are Endowed with a Decidual-Like Proangiogenic Polarization

Abstract: Natural killer (NK) cells are crucial in tumor recognition and eradication, but their activity is impaired in cancer patients, becoming poorly cytotoxic. A particular type of NK cells, from the decidua, has low cytotoxicity and shows proangiogenic functions. We investigated whether NK cells from peripheral blood (PB) and pleural effusions of patients develop decidual-like NK phenotype and whether exposure to IL-2 can restore their killing ability in the presence of pleural fluids. NK cells from pleural effusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…NK cells from human MPE exhibit poor cytotoxicity, having impaired degranulation and reduced perforin release. [122][123][124] In the malignant pleural environment, NK cells exhibit proangiogenic function, supporting capillary-like structures from recruited endothelial cells and produce angiogenic and vascular permeability inducing factors, including VEGF. 122 Interestingly, CD56 dim and CD56 bright NK cells isolated from human MPE cultured with IL-2 for 72 hours had potent antitumor cytolytic activity.…”
Section: Innate Immunity Within the Mpementioning
confidence: 99%
See 1 more Smart Citation
“…NK cells from human MPE exhibit poor cytotoxicity, having impaired degranulation and reduced perforin release. [122][123][124] In the malignant pleural environment, NK cells exhibit proangiogenic function, supporting capillary-like structures from recruited endothelial cells and produce angiogenic and vascular permeability inducing factors, including VEGF. 122 Interestingly, CD56 dim and CD56 bright NK cells isolated from human MPE cultured with IL-2 for 72 hours had potent antitumor cytolytic activity.…”
Section: Innate Immunity Within the Mpementioning
confidence: 99%
“…[122][123][124] In the malignant pleural environment, NK cells exhibit proangiogenic function, supporting capillary-like structures from recruited endothelial cells and produce angiogenic and vascular permeability inducing factors, including VEGF. 122 Interestingly, CD56 dim and CD56 bright NK cells isolated from human MPE cultured with IL-2 for 72 hours had potent antitumor cytolytic activity. 125 The same group found that IL-15 activated pleural effusion NK cells exhibited increased in vitro cytotoxicity and in vivo tumor clearance in mice.…”
Section: Innate Immunity Within the Mpementioning
confidence: 99%
“…Peripheral blood and tumor-infiltrated NK cells in cancer patients express the CD56 bright CD16 − CD49a + CD9 + phenotype (54,(58)(59)(60)(61), and they have compromised cytotoxicity (54,58,59,(61)(62)(63)(64). We have described a proangiogenic function in NK cells isolated from the peripheral blood and tumorinfiltrated cells of cancer patients (54,(58)(59)(60) and the expression of angiogenin, CXCR4/CXCL12, MMP2, MMP9, and tissue inhibitor for MMP (TIMP)-1 and TIMP-2 in NK cells from the peripheral blood and tumor-infiltrated cells of patients with colon cancer (59), which are molecules also secreted by dNK cells (55,(65)(66)(67). NK cells have been detected at low levels in the EC microenvironment (68); this study found significantly high levels of IL-1β and CXCL10 in the tumor, but low levels CXCL12, CCL27, and CCL21 as compared to the surrounding healthy tissue, and the NK cells in EC were compromised in cytotoxicity.…”
Section: Natural Killer Cellsmentioning
confidence: 99%
“…First evidence of NK cell functional plasticity in cancer highlighted the capability of TGF-β in the context of different advanced malignancies to induce a pro-angiogenic dNK cell phenotype of tumor infiltrating NK cells [76][77][78][79][80].…”
Section: Guide Of Ilc Plasticity By Tgf-β In Cancermentioning
confidence: 99%